Arsitektur Enterprise Sistem Pemerintahan Berbasis Elektronik (SPBE) Sebagai Strategi Pengembangan Smart Village Pada Dimensi Governance (Administration Service) - Alam Adhiyatama; Fitriyana Dewi; Soni Fajar Surya Gumilang (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2023)
Village development has become an important topic of discussion in Indonesia, especially with the enactment of regulations and policies that support autonomous villages. This research reviews regulations such as Presidential Regulation number 95 of 2018 concerning Electronic-Based Government Systems (SPBE) and number 6 of 2014 concerning villages that contribute to village development. Based on a survey by the Ministry of Villages of PDTT, only 4% of the total villages in Indonesia have attained the status of an Independent Village. This research identifies the need to advance information technology in villages, supports the smart village concept, and analyzes the concept of Sustainable Development Goals (SDGs) in the context of village development. One of the focuses of this research is in Rancamanyar Village, where aspects of village governance and Administration Service are the main concerns. The suggested solution is the creation of an enterprise architecture design which is expected to help the operational gaps that exist in every process in the village. This research is expected to be a guide in planning and implementing technology that supports independent and sustainable villages, as well as providing a comprehensive picture of the status of village development in Indonesia in accordance with the goals of the SDGs.